2017
DOI: 10.3389/fpubh.2017.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Consensus from the Mycobacterium avium ssp. paratuberculosis (MAP) Conference 2017

Abstract: On March 24 and 25, 2017 researchers and clinicians from around the world met at Temple University in Philadelphia to discuss the current knowledge of Mycobacterium avium ssp. paratuberculosis (MAP) and its relationship to human disease. The conference was held because of shared concern that MAP is a zoonotic bacterium that poses a threat not only to animal health but also human health. In order to further study this problem, the conferees discussed ways to improve MAP diagnostic tests and discussed potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 51 publications
0
62
0
3
Order By: Relevance
“…Based on studies, there is evidence that the etiology of the CD (in humans) and Jones disease (in the animal) have been confirmed, which include bacterial survival in commercial pasteurization methods, MAP detection in the tissues and blood of contaminated patients, increased antibody levels in sera samples of patients in the face of bacterial antigens, bacterial tracing in infected mothers, NOD2/CARD15 mutations, and response to antibiotic therapy by the macrolide family (Davis & Park, ; Kuenstner et al, ). On the other hand, there is a lack of similarities between the genotypes of bovine and human isolates, the isolation of bacteria from individuals without CD, the lack of sufficient evidence to confirm the consumption of contaminated food by patients, and the lack of transmission of bacteria from the infected mother and inactivation of bacteria causing the CD which highlight the agent existence (Mendoza, Lana, & Díaz‐Rubio, ).…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…Based on studies, there is evidence that the etiology of the CD (in humans) and Jones disease (in the animal) have been confirmed, which include bacterial survival in commercial pasteurization methods, MAP detection in the tissues and blood of contaminated patients, increased antibody levels in sera samples of patients in the face of bacterial antigens, bacterial tracing in infected mothers, NOD2/CARD15 mutations, and response to antibiotic therapy by the macrolide family (Davis & Park, ; Kuenstner et al, ). On the other hand, there is a lack of similarities between the genotypes of bovine and human isolates, the isolation of bacteria from individuals without CD, the lack of sufficient evidence to confirm the consumption of contaminated food by patients, and the lack of transmission of bacteria from the infected mother and inactivation of bacteria causing the CD which highlight the agent existence (Mendoza, Lana, & Díaz‐Rubio, ).…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…The causal link to Crohn's and other diseases has still to be conclusively proven and remains controversial (Robertson et al 2017). Kuenstner et al (2017) concluded that MAP is a zoonotic bacterium and noted that MAP present in dairy products and meat causes disease in some humans and thus poses a public health threat. If, and more probably when, MAP receives formal international recognition as a human pathogen, it will become the most thermally resistant, vegetative (nonsporulating) pathogen in milk based on its suggested decimal reduction (D) value, D 72°C of 12 s (Food Standards Agency 2002).…”
Section: Potential Significance Of Map In Milk and Milk Productsmentioning
confidence: 99%
“…Pasteurisation treatments of 77°C, 24 s; 77°C, 31 s; 78°C, 26 s and 78°C, 27 s would all be predicted to give >5 log reductions and are being used in the industry. Regardless of whether MAP causes Crohn's disease in some people (Kuenstner et al 2017), its detection in the lesions of high numbers of patients with the disease (Bull et al 2003;Naser et al, 2014) is concerning and justifies the Dairy Industry exercising the precautionary principle by voluntarily increasing the lethality of the HTST pasteurisation process for milk. In the absence of international agreement on the pathogenicity of MAP in humans, it would be prudent to expect processors to adopt at least the current European Union standards for Salmonella in ready to eat foods (European Commission 2005) and to employ a heat treatment that gives nondetectable viable MAP cells in 25 mL of milk.…”
Section: Calculation Of the Number Of Log Reductions Of Map Followingmentioning
confidence: 99%
“…Recently, an association between MAP and Crohn’s disease was shown, initiating a discussion about a possible relationship of MAP in Crohn’s pathogenesis (Alcedo et al, 2016). Johne’s and Crohn’s disease share clinical and histopathological similarities, MAP can survive standard pasteurization procedures and MAP antibodies can be detected in Crohn’s patients, where macrolide antibiotics ameliorate disease (Kuenstner et al, 2017). In contrast, genotypes of MAP isolated from cattle and man are different, there is a lack of evidence for uptake of contaminated food in respective patients and MAP cannot consistently be isolated from Crohn’s disease patients (Mendoza et al, 2009).…”
Section: Introductionmentioning
confidence: 99%